Pilonidal Disease Mimicking Fistula-in-Ano in a 15-Year-Old Female - Corey W. Iqbal; Alessandra C. Gasior; Charles L. Snyder (Case Reports in Surgery)
Pilonidal disease typically presents with an abscess or intermittent pain and drainage in the sacrococcygeal region during the pubertal years. Further examination typically reveals pits in the midline of the sacrococcyx area due to entrapment of hair with recurrent entrapment, infection, and drainage. The following paper describes an unusual presentation of a pilonidal cyst with fissure and perianal drainage.